Nivel de satisfacción de los usuarios de la Fiscalía Provincial de Los Ríos - Morán Lopez, Michell Alejandra (2021)
The Prosecutor's Office of the Province of Los Ríos, located in the Babahoyo Canton, is an autonomous law institution, whose main competence is to provide public services that guarantee impartial and timely access to the right to justice, where its management must be characterized by attention to quality and with a qualified human talent committed to ensuring the rights of citizens. For this reason, the objective of the research focuses on analyzing the level of satisfaction that users who attend the aforementioned institution have. The methodology used is constituted as follows: it has a descriptive scope; since all the findings of the investigation are narrated, the types of investigation are field and documentary; while, the techniques used as a study tool are the survey aimed at citizens to determine the quality of the service they receive and an interview with an official of the Public Prosecutor's Office, using as a resource the investigation instruments with questions aimed at obtaining the necessary information , where the following results were obtained: the availability of human talent and the speed of their functions conditions the criminal and judicial processes in the institution, the reception of the lost or citizen requests is immediate, but the speed with which The process is attended to depends on the type of crime reported, the management of the Public Prosecutor's Office does not consider the SERVQUAL model, which prevents knowing the level of user satisfaction. Public officials tend to be absent from their job for work reasons or, failing that, for personal reasons and the perception that citizens have is not adequate, they conceive that public officials do not provide the necessary conditions to access the right to access quickly and in a timely manner. Justice